Peculiarities of electrophysical properties of arsenide gallium films deposited under nonequilibrium conditions - Kabyshev, A.V.; Konusov, F.V.; Remnev, G.E.; Lozhnikov, S.N.; Saltymakov, M.S. (Ye.A.Buketov Karaganda State University Publishing house, 2010)
The electrophysical and photoelectrical properties of thin films of arsenide gallium produced by the deposition on substrate of polycrystalline corundum from the ablation plasma, formed by power ions bunch, were investigated. The annealing effect in vacuum and air on the characteristics of dark and photoconduction of films was established. Chalcogenide passivation from the alcohol solution treatment effect and followed annealing in vacuum and air effect on the electrophysical characteristics and photosensitivity of films were investigated. The conditions of the thermal and chemical treatment were determined, in which the most stable properties changes were achieved. The chalcogenide passivation allows improving the films characteristics, to stabilize them and to enhance the stability of a films surface to an oxidation in air. Work is supported by RFFI (project 08-08-12122).
Keywords: thin films; electrophysical properties; thermal and chemical treatment; oxidation in air; stability